Predicting promoters in phage genomes using PhagePromoter - Sampaio, Marta (2019)
The growing interest in phages as antibacterial agents has led to an increase in the number of sequenced phage genomes, increasing the need for intuitive bioinformatics tools for performing genome annotation. The identification of phage promoters is indeed the most difficult step of this process. Due to the lack of online tools for phage promoter prediction, we developed PhagePromoter, a tool for locating promoters in phage genomes, using machine learning methods. This is the first online tool for predicting promoters that uses phage promoter data and the first to identify both host and phage promoters with different motifs.This tool was integrated in the Galaxy framework and it is available online at: https://bit.ly/2DfebfvSupplementary data are available at Bioinformatics online.